1993
DOI: 10.1002/ajpa.1330910206
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of anemia and infection from medieval York, England

Abstract: An assessment of the presence and patterns of porotic hyperostosis and periosteal reactions in the skeletal population (n = 1,014) from St. Helen-on-the-Walls, York, are used to examine health and disease in urban medieval England. The analyses of these two lesions indicate that 58% of the population display evidence of porotic hyperostosis and that 21.5% of the population display periosteal reactions. Through differential diagnosis it is asserted that porotic hyperostosis is associated with iron-deficiency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
4

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 29 publications
2
44
0
4
Order By: Relevance
“…Walker, 1986;Blom et al, 2005;Facchini et al, 2004;Keenleyside and Panayotova, 2006), though lower prevalence in non-adults was also observed in some cases (e.g. Grauer, 1993). Subrepresentation of non-adults could not be excluded as a possible cause of lower prevalence in this age group.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Walker, 1986;Blom et al, 2005;Facchini et al, 2004;Keenleyside and Panayotova, 2006), though lower prevalence in non-adults was also observed in some cases (e.g. Grauer, 1993). Subrepresentation of non-adults could not be excluded as a possible cause of lower prevalence in this age group.…”
Section: Discussionmentioning
confidence: 89%
“…Walker, 1986;Grauer, 1993;Lovell, 1997;Wright and Chew, 1998;Piontek and Kozlowsky, 2002;Keita, 2003;Facchini et al, 2004;Blom et al, 2005;Keenleyside and Panayotova, 2006), the impact and causes of anemia in populations from southern Patagonia have been little documented. During the last decade of the 20th century, several studies reported a high frequency of porotic hyperostosis and a low frequency of cribra orbitalia in populations from Tierra del Fuego (Pérez-Pérez and Lalueza Fox, 1992;Guichón, 1994;Schinder and Guichón, 2003;Suby and Guichón, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…According to some authors (Grauer, 1993;Lewis, 2007), if a stress period lasts less than 3 months, the child can compensate the delay by catch-up growth, but if the problem lasts longer, normal growth may be irreversibly compromised. In other words, catch-up growth is related to the recovery of normal growth rate, by improved environmental conditions (Binns, 1998), or a process of habituation of the body to environmental restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…York's average rate of 26% (Table 1) is higher than the crude prevalence rate for Britain of 14.1% (Robert and Cox, 2003). A systematic study of periostitis at St. Helen-on-the-Walls found that it increased in frequency with age (Grauer, 1993). Thus, the risk of having periostitis is cumulative during life, and factors previously discussed, e.g.…”
Section: Non-specific Skeletal Evidencementioning
confidence: 98%
“…The secondary effects of these parasites, namely anaemia and, in the case of diphylobothriasis, vitamin B12 deficiency, alongside generalised high pathogen load have been linked to the prevalence of porotic hyperostosis found at the lower status cemetery of St. Helen-on-the-Walls (Grauer, 1993). Cribra orbitalia is more commonly reported than porotic hyperostosis in British collections and has also been linked to anaemia.…”
Section: Non-specific Skeletal Evidencementioning
confidence: 99%